2014
DOI: 10.1038/srep04356
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal-specific Cholesterol Reduction by Biocleavable Polyrotaxanes for Ameliorating Niemann-Pick Type C Disease

Abstract: Niemann-Pick type C (NPC) disease is an autosomal recessive lysosomal trafficking disorder, in which the cholesterols are abnormally accumulated in lysosomes. Recently, the β-cyclodextrin (CD) derivatives are revealed to show therapeutic effect for NPC disease through the removal of accumulated cholesterols in lysosomes. Herein, to enhance the therapeutic effect and reduce the toxicity of β-CD derivatives, biocleavable Pluronic/β-CD-based polyrotaxanes (PRXs) bearing terminal disulfide linkages that can releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 50 publications
2
82
0
Order By: Relevance
“…[24–26] We have previously reported that biocleavable PRXs composed of an axle polymer bearing intracellularly cleavable linkers, threading β-CDs, and bulky stopper molecules are able to dissociate in intracellular environments (Figure 1). [27] Our previous reports demonstrate that the PRX structure masks the toxic effect of β-CDs because the hydrophobic cavity of threaded β-CDs is occupied by a linear polymer chain to perturb the interaction with the plasma membranes (i.e. cholesterol in membranes).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[24–26] We have previously reported that biocleavable PRXs composed of an axle polymer bearing intracellularly cleavable linkers, threading β-CDs, and bulky stopper molecules are able to dissociate in intracellular environments (Figure 1). [27] Our previous reports demonstrate that the PRX structure masks the toxic effect of β-CDs because the hydrophobic cavity of threaded β-CDs is occupied by a linear polymer chain to perturb the interaction with the plasma membranes (i.e. cholesterol in membranes).…”
Section: Introductionmentioning
confidence: 99%
“…This local release of abundant β-CDs from the biocleavable PRXs leads to cholesterol reducing ability at a 100-fold lower concentration of clinically studied HP-β-CD and improvements in the impaired autophagy in NPC disease-derived cells. [27,28] Therefore, the biocleavable PRXs are expected to be promising noninvasive and effective therapeutics for the treatment of NPC disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Thompson and colleagues 60,61) demonstrated that pluronic-based β-CyD polyrotaxanes as well as HP-β-CyD polyrotaxanes may be promising vehicles for delivery of β-CyD and HP-β-CyD for mobilization of accumulated cholesterol from NPC fibroblasts. Moreover, Tamura and Yui 62,63) reported that β-CyD-threaded biocleavable polyrotaxanes ameliorate impaired autophagic flux in NPC. Taken together, these supramolecules may have potentials as novel drugs for the treatment of NPC.…”
Section: Hp-β-cyd For Treatment Of Niemann-pick Disease Type C (Npc)mentioning
confidence: 99%